What Influences Economic Growth in Developing Countries? A Panel Data Study - Nurhanifah, Nita Viviani (Gorontalo State University, 2025)
The global economy faces multiple crises that undermine stability and hinder growth, with developing countries being particularly vulnerable. For policymakers in these nations, achieving sustainable development is a top priority to foster long-term progress. The research attempts to establish the primary factors influencing economic growth across 11 developing countries, analyzing data spanning from 2013 to 2022. Using a fixed-effects approach in the panel data regression model, we employ GDP as a proxy for economic growth and include key variables such as public debt, trade openness, gross fixed capital formation, inflation, and population growth. The results indicate that public debt, trade openness, and gross fixed capital formation positively and significantly impact economic growth. These findings emphasize the role of capital accumulation and an open trade policy in fostering development. Conversely, inflation and population growth have significant negative effects on growth, highlighting the need for price stabilization and effective population management to avoid resource strain and inflationary pressures. Based on these results, the study recommends structural reforms and regulatory frameworks to enhance positive growth factors while addressing negative influences. Policies that encourage capital investment, maintain balanced public debt levels, and support trade openness, combined with efforts to control inflation and manage population growth, can provide a foundation for sustainable economic stability. The study ultimately underscores the importance of proactive strategies for sustaining growth and enhancing the resilience of developing countries amid global economic challenges.